(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2024)
Challenges of funding education ranks very high among many problems which have bedeviled Nigerian as a country since independence. Insufficient salaries, dearth of incentives and lack of motivation contribute to the perceived decline in the education sector. In analyzing this paper, the researchers established a problem and attributed the cause of unsustainable funding for education in Nigeria to series of variables including inconsistent policies and over dependency on oil revenue that keep fluctuating. Sources of funding education were highlighted to accommodate both individuals and governments through several channels Options for funding was viewed in terms of education as private good and public good, Challenges and way forwards were based on the analysis that government should recognize basic education (that is primary and secondary education) as public good, accepts the responsibility of providing education free for all citizen while recipients of tertiary education should be encouraged to pay for it. The paper recommended also that the private sector should be encouraged to invest in and operate the provision of education especially at tertiary level base on market demand and supply framework.